Comparative Political Marketing Comparative Political Marketing :Studi Kasus Kemenangan Paslon 01 Tatu-Pandji atas Paslon 02 Nasrul-Eki Pada Pilkada Kabupaten Serang 2020: Comparative Political Marketing :Studi Kasus Kemenangan Paslon 01 Tatu-Pandji atas Paslon 02 Nasrul-Eki Pada Pilkada Kabupaten Serang 2020 - Maharani, Renata (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2021)
This article examines the comparison of political marketing used by the candidate pair for Regent and Deputy Regent number 01, namely Ratu Tatu Chasanah and Pandji Tirtayasa to win their victory over candidate pair number 02 Nasrul Ulum and Eki Baihaki in the Regional Head Election (Pilkada) Serang Regency this year. 2020 ago. Where in the political battle that occurred in the Serang Regional Election this time was so interesting, because the political campaigns carried out by each article were carried out directly and some were carried out through new media (New Media), namely Social Media as an effort to prevent crowds in the middle of the street. in the midst of the Covid-19 pandemic. In the final election results, article number 01 came out as the winner in the contestation. Therefore, the research team conducted a search and analyzed the subject of